SISTEM PAKAR TES KEPRIBADIAN MYERS BRIGGS TYPE INDICATOR DENGAN METODE FORWARD CHAINING - Purwanto, Hari Lugis; Peri Adisa Putra (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2024)
In personality tests, a psychologist not only focuses on the assessment process and data processing but also determines the test conclusions and determines the treatment for their clients. The assessment process is often handed over to assistants so that psychologists can focus more on doing more important things. To replace the role of psychologists in conducting assessments or the same and repetitive work, an expert system is needed. Psychologists will delegate their work to a computer system to support their work so that they will focus on more essential things, thereby helping to reduce the risk of error. One of the most popular methods for personality testing is the MBTI (Myers-Briggs Type Indicator) to find the potential and weaknesses of each client so that psychologists can focus on developing potential and improving client weaknesses. MBTI will be entered into the expert system as a knowledge base. In finding answers, the inference engine will track by matching knowledge-based rules with facts in the database using the forward chaining method. And as a result, the software that has been built can be used to analyze personality tests. The information generated helps psychologists to analyze human personality tests and be more efficient in dealing with client problems. Clients are also able to conduct independent tests to identify their own weaknesses and strengths, so that the development suggestions provided by the system can be used as a guide in suppressing their negative side and maximizing their positive side.